A giant frontal cavernous malformation with review of literature - Sharma, Arvind (J Neurosci Rural Pract, 2016)
Cavernous malformations (CMs) are vascular anomalies with dilated spaces called caverns. These spaces are lined by endothelial cells and collage and devoid of smooth muscle or intervening neural tissue, and filled with blood at various stages of stasis, thrombosis, organization, and calcification. Most CMs are relatively small in size but when they are large enough they can produce sing of mass effect and may simulate neoplastic, vascular, inflammatory pathology. Giant CM (size >6 cm) are very rare lesions and very few cases are reported in world literature. We are reporting such a rare case of a 16 year male. Our case is also unique in the sense that it is the largest reported CM in Indian population.